Energy drink consumption among Korean adolescents: prevalence and associated factors - Jee-Seon Shim; Jeong Mi Lee (Clinical and Experimental Pediatrics)
Background Energy drinks are gaining popularity among young people worldwide. However, little is known about their consumption among Korean adolescents. Purpose To examine the prevalence and factors associated with energy drink consumption among Korean adolescents. Methods This study used data from the Korea Youth Risk Behavior Surveys conducted in 2014–2017 and in 2019. A total of 325,210 participants aged 12–18 years were included. The prevalence of energy drink consumption (with 95% confidence intervals) was estimated. Multivariable logistic regression analyses examined the association between energy drink consumption and sociodemographic and individual factors. Results The prevalence of consuming energy drinks 3 or more times during the previous 7 days increased significantly from 3.2% in 2014 to 12.2% in 2019 (P for trend<0.001). This increasing trend was observed in all subgroups regardless of sex, school grade, region of residence, subjective economic status, family cohabitation status, and academic achievement. Data from the 2014–2017 and 2019 surveys revealed that boys, high schoolers, city-dwelling adolescents, adolescents with low economic status, those not living with their families, and those with low academic achievement were more likely to consume energy drinks. However, the relationship between energy drink consumption and the associated factors differed by survey year and school grade. In 2019, higher energy drink consumption among middle schoolers was associated with sex (male), low economic status, not living with family, and low academic achievement; however, higher energy drink consumption among high schoolers was associated with city-dwelling, high economic status, not living with family, and high academic achievement. Conclusion Energy drink consumption is common, has recently increased among Korean adolescents, and varies according to sociodemographic and individual factors. Further research to monitor the energy drink consumption of adolescents and understand their attitudes toward and factors influencing energy drink consumption is needed to develop policies and educational strategies for energy drink consumption.